Pengaruh Terapi Murottal Al-Qur’an Terhadap Tingkat Hipertensi Pada Lansia Di Rw 001 Kampung Gurudug Desa Mekar Jaya Kabupaten Tangerang - adinda intan adinda intan safitri; Siti Rochmani; Lastri Mei Winarni (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2022)
ABSTRACT Background: Hypertension is the second leading cause of death after stroke from the death population in Indonesia. The incidence of hypertension reaches 30% with the incidence of heart disease. Hypertension can be treated with two types of therapy, namely pharmacological and non-pharmacological. Researchers use therapy related to rituals in Islam, namely listening to the Qur'an. Murottal therapy can improve healing and lower blood pressure in hypertensive patients. Murottal can read the Qur'an on the truth of reading the Qur'an. The purpose of the study: To determine the effect of murottal Al-Qur'an therapy on the level of hypertension in the elderly in RW 001, Gurudug village. Methods: this research is quantitative research using pre-experimental research design, one group pretest-posttest design. This study was conducted in a week and performed the first blood pressure measurement, the intervention was listening to murottal Al-Qur'an therapy and then taking the second blood pressure measurement. The data instrument is in the form of interviews with a population of 87 elderly people in RW 001 Kampung Gurudug, Mekar Jaya Village, Tangerang Regency. The sample is 64 elderly using simple regression analysis. Results: the results show a significance value of 0.001 < 0.05, this indicates that there is an effect of murottal Al-Qur'an therapy on the level of hypertension. Conclusions and suggestions: it can be concluded that there is a significant difference between blood pressure before and after murottal Al-Qur'an therapy in the elderly. Keywords: Al-Qur'an murottal therapy, hypertension, elderly.